TREATMENT OF METABOLICLY ASSOCIATED FATTY LIVER HEPATOSIS IN THE YOUNG POPULATION (CAHIERS MAGELLANES-NS, 2024)
One of the main pathogenetic signs of metabolic syndrome is abdominal obesity, which underlies the development of diseases associated with metabolic disorders - carbohydrate metabolism disorders and atherogenic dyslipidemia. The presence of abdominal obesity and metabolic disorders contributes to the development of combined damage to the liver (non-alcoholic fatty liver disease - NAFLD), biliary tract, heart, and pancreas (with the development of steatosis).